Analysis of the Management Information System Application Related with Service Data at Hajj Regional General Hospital of Makassar - Thabran Talib, Muhammad; Meilany, Lilik; Sukawan, Ari (KnE Life Sciences, 2021)
This study analyzes the information system at the Hajj Regional General Hospital of Makassar as a service that is needed for both professional health workers and the served community. The information is about service achievement targets, managerial strategic planning, efficiency and effectiveness of health services.This study aims to obtain information service data that will be utilized by a Management Information System (MIS) which includes computerization needs, information personnel, usage of computers and information system support. The research design is a descriptive survey which was conducted from July to August 2019 and data collection was performed by using questionnaires, observation and document review. The results of the study from 50 respondents showed that 29 respondents (58%) filled in basic data as service data information was very high and very complete (79.87%.) Application of the hospital MIS based on the need for computerization and MIS personnel is very high, which are 88.87% and 89.96%. MIS has a great position and is more important in the hospital business industry due to service information is an indication of health service standards. Hospital MIS is an information system that performs all transaction management therefore information management has results in decision making by providing an indicator for the appearance of health services.One of its functions is to handle the recording of service costs, both for action and medication starting from outpatient care until the patient is discharged from the hospital. This research focuses on inpatient service data information that will be used as MIS, which includes computerization needs, information personnel, and the usage of computers and supporting information systems. Our study revealed that the application of MIS at Hajj Regional General Hospital of Makassar must be supported by the media of communication devices, application programs and human resources who have the profession in information systems and advice, the leadership and administrators that will improve the efforts of MIS which can be handled professionally to create an orderly administration, management and advance the quality of health services. Keywords: Information Systems, Management, Service Data